1990
DOI: 10.1093/infdis/162.5.1087
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Polyclonal Sera and of Monoclonal Antibodies Active to Salmonella minnesota Re595 Lipopolysaccharide during Experimental Endotoxemia

Abstract: Mice were passively immunized with sera from blood donors active for rough lipopolysaccharides (LPS), the J5 (Rc chemotype) mutant of Escherichia coli O111:B4, and the Re595 (Re chemotype) mutant of Salmonella minnesota. All protected the mice against lethal challenge with smooth E. coli WF96 LPS, E. coli and Salmonella rough mutant LPS, or free lipid A. Epitopes recognized by monoclonal antibodies (MAbs) reacting with the LPS of S. minnesota Re595 or lipid A were localized in the 2-keto-3-deoxy-D-manno-octulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…153 The protective serum fractions, however, failed to provide significant protection against the S-form LPS of S. enteriditis. In an earlier section, we have discussed the evidence that E. coli 07:K1 possesses rough or semirough LPS, rather than the S-form type.…”
Section: Rough-mutant Vaccines: Historical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…153 The protective serum fractions, however, failed to provide significant protection against the S-form LPS of S. enteriditis. In an earlier section, we have discussed the evidence that E. coli 07:K1 possesses rough or semirough LPS, rather than the S-form type.…”
Section: Rough-mutant Vaccines: Historical Perspectivementioning
confidence: 99%
“…48 Nys et al reported that J5 and R595 rabbit antisera protected actinomycin D-sensitized mice against lethality from E. coli 07 LPS, but not from S. enteriditis LPS. 153 Whether this represents another example of selective protection or is relatable to differences in titers of 0 antibodies was not explored.…”
Section: Rough-mutant Vaccines: Historical Perspectivementioning
confidence: 99%
“…To measure the eects of antibodies during endotoxemia, we chose two endotoxin models using chemically characterized LPS [33]. Both these models have been used previously successfully, by ourselves and others [4,19,29,41]. The ®rst used mice sensitized to the lethal eects of LPS by actinomycin D or mice challenged with i.p.-injected bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Eects on LPS-induced mortality were estimated using actinomycin D-treated mice as previously described [41]. Brie¯y, serial dilutions of a 1 mg/ml stock suspension of LPS (S and R forms) were prepared in pyrogen-free physiological saline immediately prior to administration.…”
Section: Lethality Studiesmentioning
confidence: 99%
“…This result was soniewhat enigmatic, since the animals were colonized by several putative periodontal pathogens in addition to P. gingivalis (43). We suspected that, since gram-negative pathogens can express shared antigenic epitopes especially in lipopolysaccharide (12,14,26,36,42) and antibodies to these epitopes can be protective (3,26,36,38), immunization with one species could induce an immune response to antigens of multiple species, thereby accounting in part for the protection observed. We tested this hypothesis using sera from monkeys previously immunized with P. gingivalis (43) and sera from rabbits immunized with either P. gingivalis, B. forsythus or A. actinomycetemcomitans.…”
mentioning
confidence: 99%